Effect of reinforcement volume fraction on the mechanical properties of the al-sic composite - Mohamad Amirul Aliff, Yahya (2016)
This thesis mainly focuses on the effect of reinforcement volume fraction on the mechanical properties of Al-SiC composite. Nowadays, there are many approach is used to enhance the mechanical properties of composite. The only argument is which method will deliver the most effective result and exhibited better mechanical properties. The decrease in volume fraction of SiC particle increase its ductility but the hardness is decrease. Therefore, the objectives of this thesis is to investigate the effect of volume fraction on the mechanical properties of Al-SiC and to optimize the mechanical properties of Al-SiC to obtain optimum volume fraction. The experiment was carried out by the powder metallurgy process. The raw materials was mixed and compact in the hydraulic press to make the green compact samples. After that the samples were sintered in the sintering furnace. The samples were prepared with 10 and 15 vol% of the SiC particles. 20 Ton load was used as the compaction load of all the samples. After that the samples were prepared for the mechanical testing and microstructure observation. The microstructure was observe in the optical microscope. The density and hardness of the samples were measured and compared. The hardness was measured by the Vickers micro hardness testing machine as per the ASTM e348. The results showed that the 15 vol% of SiC reinforcement provided better mechanical proper as compared to the other volume fraction of the reinforcement.